Facial soft tissue changes in adolescent patients treated with three different functional appliances: a randomized clinical trial - Nathália Moraes Carvalho Barreto BRANDÃO; Nathália Barbosa PALOMARES; Tatiana LIMA; Cátia Cardoso Abdo QUINTÃO; Klaus Barretto LOPES; José Augusto Mendes MIGUEL (Dental Press Editora, 2024)
ABSTRACT Introduction: Patients with Class II, division 1 malocclusion generally seek treatment to improve facial esthetics. Therefore, the orthodontist needs to know the changes in the soft profile produced by functional appliances. Objective: This study evaluated the soft tissue profile changes in patients treated during the peak of the pubertal growth spurt. Methods: Thirty selected patients were randomized into three treatment groups: Twin Block (TB), Herbst with dental anchorage (HDA), and Herbst with skeletal anchorage (HSA). All patients had computed tomographic images: pretreatment (T1) and after 12 months of active treatment (T2). Twenty-four soft tissue cephalometric measures were analyzed. The normality of all data was assessed by the Shapiro-Wilk test. Intragroup comparisons were analyzed using the t-paired test; the inter-group comparisons were determined through ANOVA and the post-hoc Tukey test. Results: At T1, no significant differences were observed between groups. At T2, in the intragroup comparison, facial soft tissue changes were statistically significant in the three groups for the lower lip, sulcus inferioris, facial soft tissue convexity in HDA group and TB group, and H angle in HDA group and HSA group, and soft tissue pogonium in TB group. In the inter-group comparison, no statistically significant differences were observed. Conclusion: It can be concluded that there were significant changes in soft tissue measurements that benefited Class II, division 1 patient's facial profile treated with the functional appliances Twin Block, Herbst, and Herbst with skeletal anchorage. Nevertheless, no significant differences were detected among the effects obtained by the three treatment protocols.